Elliptic Aperture Coaxial Sensor - Haiba A. Ehtaiba, Mabrouka (International Journal of Engineering Research, 2023)
Flat open-ended coaxial sensors are increasingly popular for numerous measurement techniques, as a non-destructive method, due to the increased sensitivity and contrast obtained at microwave frequencies. The flat aperture of the sensor limits the practical application of such a method, particularly in diagnosis. In this paper, an elliptic aperture coaxial sensor with small dimensions is introduced and numerically analysed. Using finite element method, the radiation from the elliptical aperture into a two-layer dielectric medium is examined. Explicit contrast of reflection coefficient in both magnitude and phase, and high sensing depth are obtained with such a sensor aperture at low microwave frequencies of 0.1, 0.3, 1, and 3 GHz.